Chick flick / Muhammad Yusuf Haikal Ismail ...[et al.] - Ismail, Muhammad Yusuf Haikal; Nik Ruseli, Nik Muhammad Faez Ikhwan; Azlan, Nur Ami Syafinaz; Mohammad Redhuan, Nur Farzana; Sanusi, Wardatus Sofiah (2023)
Chick Flick is a company that sells frozen chicken wings in Kampung Pasir Putih, Pasir Gudang, Johor. Chick Flick chose this area since it is well-known and accessible to anyone. At a reasonable price, Chick Flick sell halal frozen chicken wings in a range of flavours such as buffalo chicken wings, soy garlic chicken wings, and barbecue chicken wings. The goal of the company is to meet the demands of our customers. To be healthy, for example, design frozen food products that are nutritious, low in sugar and fat. We chose frozen chicken wings as our business since everyone nowadays enjoys chicken wings, especially young people and children. Chicken wings are also quite popular among Malaysians since it has a particular position among Malaysians of all ages. Moreover, it has a high demand for chicken wing that make it easy to sell. The company's headquarters are in Pasir Gudang. Chick Flick chose to open a business there since it is one of the cities with the biggest concentration of higher education students, residents, and workers. Our goods will be available for purchase every Monday through Saturday from 7 a.m. to 7 p.m. The uniqueness of Chick Flick product is, Chick Flick use homemade recipes which is from mother of one of our members. Chick Flick also will introduce combo flavour’s which is it have more than 1 flavour in one pack. Frozen chicken wings from Chick Flick also come with ready to eat sauce. We assess and plan by category after finishing the company planning. Marketing, operational, organisational, and finance are the categories. We also perform business model canvas to have a deeper understanding of the planning. The Company Model Canvas is a strategic management tool for building new or existing business models